Um modelo de otimização para o problema de alocação de rota e espectro em redes ópticas elásticas - Araujo, Carlos Magno de Oliveira (2018)
Elastic optimal networks appeared as an alternative to traditional WDM optimal networks, where the optimal spectrum is organized in static wavelengths. Recent technologies allowed for a new way of using the optical spectrum, dividing it in low traﬃc rate subcarrier bands that admit orthogonality overlap (OFDM). This new approach motivated the need of developing novel algorithms that should be designed to cope with the ﬂexibility of elastic optical networks. The RSA problem, which is NP-hard, aims at eﬃciently using the optical spectrum while meeting the traﬃc demands in this type of networks. This work proposes a new multi-commodity ﬂow-based integer linear programming model for a version of the RSA problem. Computational experiments show that both approaches presented good performance when compared to the main proposed approach on the literature for the addressed problem.